State-dependent and site-directed photodynamic transformation of HCN2 channel by singlet oxygen - Gao, Weihua; Su, Zhuocheng; Liu, Qinglian; Zhou, Lei (The Journal of general physiology, 2014)
Singlet oxygen (1O2), which is generated through metabolic reactions and oxidizes numerous biological molecules, has been a useful tool in basic research and clinical practice. However, its role as a signaling factor, as well as a mechanistic understanding of the oxidation process, remains poorly understood. Here, we show that hyperpolarization-activated, cAMP-gated (HCN) channels–which conduct the hyperpolarization-activated current (Ih) and the voltage-insensitive instantaneous current (Iinst), and contribute to diverse physiological functions including learning and memory, cardiac pacemaking, and the sensation of pain–are subject to modification by 1O2. To increase the site specificity of 1O2 generation, we used fluorescein-conjugated cAMP, which specifically binds to HCN channels, or a chimeric channel in which an in-frame 1O2 generator (SOG) protein was fused to the HCN C terminus. Millisecond laser pulses reduced Ih current amplitude, slowed channel deactivation, and enhanced Iinst current. The modification of HCN channel function is a photodynamic process that involves 1O2, as supported by the dependence on dissolved oxygen in solutions, the inhibitory effect by a 1O2 scavenger, and the results with the HCN2-SOG fusion protein. Intriguingly, 1O2 modification of the HCN2 channel is state dependent: laser pulses applied to open channels mainly slow down deactivation and increase Iinst, whereas for the closed channels, 1O2 modification mainly reduced Ih amplitude. We identified a histidine residue (H434 in S6) near the activation gate in the pore critical for 1O2 modulation of HCN function. Alanine replacement of H434 abolished the delay in channel deactivation and the generation of Iinst induced by photodynamic modification. Our study provides new insights into the instantaneous current conducted by HCN channels, showing that modifications to the region close to the intracellular gate underlie the expression of Iinst, and establishes a well-defined model for studying 1O2 modifications at the molecular level.